Peran Tradisi Irung-Irung dalam Memperkuat Civic Engagement Generasi Muda di Kabupaten Bandung Barat - Nanggala, Agil; Malihah, Elly (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
This study aimed to analyze the role of the irung-irung tradition in strengthening civic engagement of the younger generation of Cihideung Village. This study used a qualitative approach with the case study method. Data collection techniques used interviews, observations, and literature studies. The results showed that the traditional irung-irung procedure: praying together, marching to water resources, custom ceremonial process, sacrificing animals, eating together, and closing prayers, the younger generation’s involvement in the irung-irung tradition was more focused on the aspect of democracy through the positive role it plays, not yet at the traditional level, the strategy for strengthening the engagement of the younger generation was through the empowerment of youth and utilizing information and communication technologies.